2013
DOI: 10.1186/1475-2840-12-124
|View full text |Cite
|
Sign up to set email alerts
|

Additive relationship between serum fibroblast growth factor 21 level and coronary artery disease

Abstract: BackgroundExpression and activity of the fibroblast growth factor (FGF) 21 hormone-like protein are associated with development of several metabolic disorders. This study was designed to investigate whether serum FGF21 level was also associated with the metabolic syndrome-related cardiovascular disease, atherosclerosis, and its clinical features in a Chinese cohort.MethodsTwo-hundred-and-fifty-three subjects visiting the Cardiology Department (Sixth People's Hospital affiliated to Shanghai JiaoTong University)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
103
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 22 publications
5
103
1
1
Order By: Relevance
“…Our findings have expanded the current understanding on the relationship between serum FGF21 and CHD. Several cross‐sectional studies had shown that serum FGF21 levels were significantly higher in subjects with CHD than those in controls 13, 14. In a study involving 100 Chinese subjects, with 38% of them having T2DM, serum FGF21 levels were independently associated with the presence of acute myocardial infarction and were significantly higher in those who developed reinfarction within 30 days 15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings have expanded the current understanding on the relationship between serum FGF21 and CHD. Several cross‐sectional studies had shown that serum FGF21 levels were significantly higher in subjects with CHD than those in controls 13, 14. In a study involving 100 Chinese subjects, with 38% of them having T2DM, serum FGF21 levels were independently associated with the presence of acute myocardial infarction and were significantly higher in those who developed reinfarction within 30 days 15.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, the association of circulating FGF21 with CHD in T2DM has not been clearly defined. In cross‐sectional studies, conflicting results were reported regarding circulating FGF21 levels in subjects with CHD, with an association of raised FGF21 levels with CHD reported in some studies,13, 14, 15 but not in others 16, 17. The association of circulating FGF21 with CHD in T2DM, especially among those without known cardiovascular disease (CVD), remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Available data on gender differences in FGF-21 concentration in non-diabetic population vary widely: from equal FGF-21 concentration [24,25] to lower [21] and higher FGF-21 concentration in women [26,27].…”
mentioning
confidence: 99%
“…FGF21 currently receives general interest as one of the most promising clinical anti-diabetic drug candidate [4], but, paradoxically, circulating endogenous FGF21 is elevated during obesity [48,49], type 2 diabetes [50], and coronary artery disease [51]. In contrast, its induction and secretion from skeletal muscle in response to mitochondrial perturbations and ISR activation [8e11] raised the idea of an adaptive mitochondrial stress-related pseudo-starvation response via endogenous FGF21.…”
Section: Discussionmentioning
confidence: 99%